The adoption of ISO 45001: 2018 in the civil aviation establishment test and its accessibility to the standard - فاضل, قصي عبدالخالق; جمعة, محمود حسن; نوري, حيدر شاكر (Journal of Economics and Administrative Sciences, 2019)
The current research aims to analyze the extent of the adoption of the standards of ISO 45001: 2018 for occupational safety and health management by the General Establishment of Civil Aviation. The research problem was the extent to which the General Establishment of Civil Aviation approved ISO 45001: 2018 for occupational safety and health management. The questionnaire was used as a primary data collection tool, the sample was distributed (50) form, they were selected from the category of employees of the establishment at different levels to represent the research community. Data were analyzed using the statistical package (SPSS), a number of vector statistical methods were used as well as arithmetic mean, standard deviation, and coefficient of variation. The research found a number of conclusions, the most important of these was that the Quality Management Department at the General Establishment of Civil Aviation has a good knowledge of the requirements of ISO 45001: 2018 for the management of occupational safety and health and seeks to obtain it. The research produced a set of appropriate recommendations.